Communication Model in the Online Learning Process During the Covid-19 Pandemic at University - Hanafi, Muhammad Yusuf (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to find a communication model in online learning at the Faculty of Da'wah and Communication Studies, the Master's Program at the State Islamic University of North Sumatra, Medan. The method used in the application of the communication model in the online learning process at the Master's Program in Da'wah and Communication Studies at the State Islamic University of North Sumatra Medan, with a qualitative case study model method, research data in the form of a learning process using a communication model during. The data source was obtained from the UINSU Da'wah faculty master program; observation, interviews, and documentation used data collection techniques. Data analysis was done by data reduction, presentation, and conclusion. The communication pattern used in the online learning process at the Faculty of Da'wah and Communication in the Master's Program at the North Sumatra State Islamic University of Medan in applying the communication model is one-way and two-way. During the Covid 19 Pandemic, android media had to be used through Zoom accounts, Google Classrooms, Google Meet, and various other accounts such as WA and email. In this case, one solution is to carry out the learning process online in the hope that face-to-face lectures can be immediately conducted for students, and another solution is to provide package assistance to underprivileged students through the Ministry of National Education's assistance.